Study on the effect of pore-scale heterogeneity and flow rate during repetitive two-phase fluid flow in microfluidic porous media. Issue 2 (2021) - Zhang, Jingtao; Zhang, Haipeng; Lee, Donghee; Ryu, Sangjin; Kim, Seunghee
No abstract available